Redefining Family: Alternative Family Narratives in Hirokazu Koreeda's Manbiki no Kazoku (Shoplifters) - Wawat Rahwati; Rima Devi; Aulia Asyifa (Journal of Language and Literature, 2026)
This article explores an alternative family narrative in the Japanese film Manbiki no Kazoku (Shoplifters, 2018) by Hirokazu Koreeda. This film portrays a group of marginalized individuals living together as a family despite lacking legal marriage and blood ties. Through an analysis of the film's narrative, this research examines how the alternative family dynamic is presented in Manbiki no Kazoku. Using a literary sociology approach, the analysis applies social exclusion theory to contextualize the Shibata family’s marginalization within broader issues of poverty, neglect, and precarity in contemporary Japanese society. The results reveal that Koreda’s narrative challenges conventional Japanese kinship structures by presenting a “chosen family” that fulfills essential functions of emotional support and socialization. The film shows how the idea of an alternative family grows out of the characters’ experience of social exclusion. Unlike the Japanese Ie system and nuclear family, which depend on blood ties and legal marriage for legitimacy, the Shibata family comes through shared experience and solidarity of individuals living on the margin of society. By situating the film within debates on social exclusion and the transformation of family in modern Japan, the study demonstrates that Manbiki no Kazoku (Shoplifters) redefines family as a flexible institution grounded in solidarity and mutual responsibility, offering a narrative as a form of negotiation to face the social problems in Japanese society.